ANALISIS STRATEGI BISNIS UNIT / DISTRIK SERDANG PT. PERKEBUNAN NUSANTARA III MEDAN - Johan, T.Syahmi; Siregar, Tumpal HS; Hafiz, Faoza (Universitas Medan Area, 2012)
The strategy is an action that is incremental (constantly increasing) and continuously, and is based on the customer expected in the future. The speed of innovation of new markets and changing patterns of consumer requires core competencies. This research was conducted at PT. PTPN III Serdang District II (DSER 2), with the objectives of : (1) to analyze the strengths, weaknesses, threats and opportunities the business units of PTPN III, (2) to identify the business strategies implemented by each business unit/district in PTPN III, as one of the incremental actions and continous for the customers expectations towards the products.The results showed that: (1) based on internal factor analysis, the strengths and the weaknesses of the business unit District of Serdang II are the high sales value, healthy financial condition, organizational structure, educational background, soil fertility and plant age composition.While the weakness of the business unit are the age composition of employees, competitive HPP and activity based costing, (2) the opportunities and threats in the business unit Serdang District II are the development of downstream industries, foreign currency appreciation, global cultural phenomenon, waste utilization and increased market share. While the threat of the business unit are the environment business security, economics and the global financial crisis, the competitor technology development, product availability substitution, selling price volatility changes and consumer demand, (3) the business unit Serdang District II has the strengths to increase the productivity through the optimization aspects of culture and technology plants, improving coordination and synergy with related parties in the cost efficiency of every business activity and encourage the improvement of the quality and competence of the Human Resources (HR), (4) the business strategy that can be done by business unit Serdang District II are the aggressive strategy intensive, vertical integration and strategy diversifrkasi. By the three alternative strategies that have been, the intensive strategy is the main option to be implemented, the integration strategy and diversification strategy. Keywords : strategy, incremental, continuous and customer orientation